2017
DOI: 10.1007/s10096-017-3110-9
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal colonization with resistant bacteria: a prognostic marker of mortality in decompensated cirrhosis

Abstract: Infections due to drug-resistant (DR) bacteria are increasingly recognized as an emerging problem worldwide. Asymptomatically colonized patients may contribute to the reservoir in the hospital setting, causing both horizontal transmission and endogenous infections. We aimed to evaluate the prevalence of intestinal colonization with DR bacteria on subsequent clinical infection development and prognosis in patients with decompensated cirrhosis. One hundred seven patients without infection at baseline were screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Bacterial metabolites that reach the liver through portal system activate toll-like receptors (TLRs)[ 18 ], and the genetic polymorphism of TLR and nucleotide-binding oligomerization domain 2 genes may also be involved in the pathogenesis of BT, thus increasing the risk of infection in patients with LC by altering TLR binding to lipopolysaccharides or endotoxins[ 13 , 16 ]. Finally, intestinal colonization and translocation of drug-resistant bacteria may induce MDR SBP infections[ 19 , 20 ].…”
Section: Bacterial Infections In Patients With Liver Cirrhosismentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial metabolites that reach the liver through portal system activate toll-like receptors (TLRs)[ 18 ], and the genetic polymorphism of TLR and nucleotide-binding oligomerization domain 2 genes may also be involved in the pathogenesis of BT, thus increasing the risk of infection in patients with LC by altering TLR binding to lipopolysaccharides or endotoxins[ 13 , 16 ]. Finally, intestinal colonization and translocation of drug-resistant bacteria may induce MDR SBP infections[ 19 , 20 ].…”
Section: Bacterial Infections In Patients With Liver Cirrhosismentioning
confidence: 99%
“…In two series of patients with LC evaluated in 2005-2007 and 2011-2012, Fernández et al[ 33 ] reported that MDR bacteria were more common in nosocomial infections and were associated with higher in-hospital mortality than in infections caused by antibiotic-susceptible bacteria. Pouriki et al[ 20 ] reported drug-resistant bacteria in intestinal cultures from 44% of uninfected patients with decompensated LC. Recent reports have found that asymptomatic intestinal colonization with MDR or XDR bacteria was an increased mortality risk in patients with LC in part because of BT of circulation of bacterial components[ 20 ].…”
Section: Bacterial Infections In Patients With Liver Cirrhosismentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 18 It has been utilized to characterize the gut microbiota in healthy adults and infants as well as in diseased states including inflammatory bowel diseases, acute pancreatitis, and critical illness. 17–21 Although rectal swabs have been used in cirrhosis to detect specific drug-resistant pathogens using traditional culture techniques, 22 , 23 to our knowledge, no study has utilized rectal swab to comprehensively survey the gut microbiome via sequencing-based technologies in cirrhosis. In this study, we set out to compare luminal and mucosally adherent gut microbiota in cirrhosis via stool and rectal swab, respectively, using shotgun metagenomic sequencing, with the notion that observed differences might be reflective of the different microenvironments in which they reside.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infections are frequent complications in patients with decompensated cirrhosis, and are the most frequent triggers of spontaneous bacterial peritonitis, urinary tract infections, pneumonia, and cellulitis (1). Bacterial infection, a risk that is magnified in these patients, increases the rate of short-term mortality, being the most frequent cause of death (2). Recently, multidrug-resistant (MDR) bacterial infections are in an alarming increase in patients with decompensated cirrhosis (3).…”
Section: Introductionmentioning
confidence: 99%